A regulatory perspective on the influence of health information technology on organisational quality and safety in England. (June 2020) - Martin, Guy; Arora, Sonal; Shah, Nisha; King, Dominic; Darzi, Ara
Health information technology can transform and enhance the quality and safety of care, but it may also introduce new risks. This study analysed 130 healthcare regulator inspection reports and organisational digital maturity scores in order to characterise the impact of health information technology on quality and safety from a regulatory perspective. Although digital maturity and the positive use of health information technology are significantly associated with overall organisational quality, the negative effects of health information technology are frequently and more commonly identified by regulators. The poor usability of technology, lack of easy access to systems and data and the incorrect use of health information technology are the most commonly identified areas adversely affecting quality and safety. There is a need to understand the full risks and benefits of health information technology from the perspective of all stakeholders, including patients, end-users, providers and regulators in order to best inform future practice and regulation.